Model and Empirical Study on Multi-tasking Learning for Human Fall Detection - Duc-Anh Nguyen; Cuong Pham; Rob Argent; Brian Caulfield; Nhien-An Le-Khac (Vietnam Journal of Computer Science, 2024)
Many fall detection systems are being used to provide real-time responses to fall occurrences. Automated fall detection is challenging because it requires very high accuracy to be clinically acceptable. Recent research has tried to improve sensitivity while reducing the high rate of false positives. Nevertheless, there are still limitations in terms of having efficient learning approaches and proper datasets to train. To reduce false alarms, one approach is to add more nonfall data as negative samples to train the deep learning model. However, this approach increases class imbalance in the training set. To tackle this problem, we propose a multi-task deep learning approach that divides datasets into multiple training sets for multiple tasks. We prove this approach gives better results than a single-task model trained on all datasets. Many experiments are conducted to find the best combination of tasks for multi-task model training for fall detection.